Community Empowerment Through the Inheritance of Scavengers' Work Culture Values in Surabaya City - Heryanto Susilo; Yatim Riyanto; Widya Nusantara; Mustakim Mustakim; Fina Akmalia Putri (Journal of Nonformal Education, 2026)
Urban marginalized populations, particularly those engaged in scavenging, encounter significant socioeconomic barriers notwithstanding their crucial role in urban waste management and the promotion of environmental sustainability. These groups uphold essential values intrinsic to work culture, like diligence, accountability, resilience, collaboration, and adaptability, which are conveyed through intergenerational social interactions. The aims to explore how the legacy of scavengers' work culture values facilitates community empowerment in Surabaya City. A qualitative methodology grounded in theory was employed for this inquiry. Data collection involved purposive sampling of scavenger families, community leaders, and relevant stakeholders, utilizing in-depth interviews, participant observation, and document analysis. The analysis was conducted through open, axial, and selective coding to construct a comprehensive explanatory framework. The results that the transmission of work culture values occurs via familial socialization, firsthand work experiences, and communal interactions. Such values bolster individual resilience, amplify the significance of work, promote collective engagement, enhance economic adaptability, nurture social solidarity among scavenger families. The transmitted values foster environmental consciousness and support sustainable livelihoods through ongoing generational knowledge exchange. The conclusion, the intergenerational transfer of work culture constitutes a sustainable mechanism for community empowerment, thereby enhancing social cohesion and contributing to the enduring welfare of marginalized urban populations.